Apparent ileal digestiblity of amino acids and digestible and metabolizable energy valves for conventional soybean meal or dry extruded-expelled soybean meal for swine - Woodworth, J.C.; O'Quinn, P.R.; Knabe, D.A.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We conducted two experiments to determine the apparent ileal digestibility of amino acids and digestible energy (DE) and metabolizable energy (ME) values for conventionally processed, solvent-extracted soybean meal (SBM) compared to dry-extruded-expelled SBM with or without soy hulls. Apparent ileal digestibility of crude protein and lysine and DE and ME values were greater in either extruded-expelled SBM compared to the conventionally processed SBM. No differences occurred in apparent digestibility of amino acids or energy values between extruded-expelled SBM with hulls and that without hulls. These results suggest that the dry extrusion followed by expeller processing of soybeans results in a SBM with slightly greater digestibility of crude protein and lysine as well as greater DE and ME values con1pared to conventionally processed, solvent-extracted SBM.
Keywords: Swine; Soybean meal; Processing; Digestability; Energy